2019
DOI: 10.1177/1179546819878680
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Induced Acute Kidney Injury: Review and Practical Update

Abstract: Contrast-induced acute kidney injury (CI-AKI) is an important consideration in patients undergoing cardiac catheterization. There has been a continuous strive to decrease morbidity and improve procedural safety. This review will address the pathophysiology, predictors, and clinical management of CI-AKI with a concise overview of the pathophysiology and a suggested association with left atrial appendage closure. Minimizing contrast administration and intravenous fluid hydration are the cornerstones of an effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 63 publications
0
56
0
7
Order By: Relevance
“…A previous study showed that CI-AKI is associated with major adverse clinical outcomes and death [5]. Once CI-AKI occurs, there is no specific treatment; hence, prevention by minimizing contrast administration and Intravenous (IV) fluid hydration is the optimal management strategy [6]. However, clinical data regarding their feasibility, efficacy, and safety are limited [7].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that CI-AKI is associated with major adverse clinical outcomes and death [5]. Once CI-AKI occurs, there is no specific treatment; hence, prevention by minimizing contrast administration and Intravenous (IV) fluid hydration is the optimal management strategy [6]. However, clinical data regarding their feasibility, efficacy, and safety are limited [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the incidence of CIN was 3%, and more than 50% of patients experienced CIN for high-risk individuals following PCI [ 19 21 ]. Although the mechanism is not yet clear, however, it is believed that the complication is closely related to renal hemodynamic changes, toxic injury of renal tubular epithelial cells, and decrease in nitric oxide production, intracellular calcium overload, and oxidative stress [ 22 24 ]. According to the different pathogenesis, many therapies on preventing CIN have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vasoconstriction is known to increase blood viscosity after CM administration. CM increased viscosity and tubular pressure, exacerbating renal hypoperfusion and promote a decrease in urine flow rate, leading to its retention and allowing its continuous cytotoxicity [ Figure 1] [64,65] . Furthermore, blood viscosity is a key player in CVD pathophysiology and is associated with increased risks of CVD [66,67] .…”
Section: Cin Pathophysiology In the Context Of Cvdmentioning
confidence: 99%